Effects of two marine dietary supplements with high calcium content on calcium metabolism and biochemical marker of bone resorption - Lecerf, J.M; Lamotte, C; Boukandoura, B; Cayzeele, A; Libersa, C; Delannoy, C; Borgiès, B (European journal of clinical nutrition, 2008)
Background/Objective: Calcium is essential for the bone metabolism but daily calcium requirements are not met in a significant proportion of the population. Fortunately, oral calcium supplementation can help to meet these needs; however, the calcium bioavailability depends on the calcium sources. The calcium absorption and bioavailability of dietary supplements from marine sources are not known. The objectives of this study were to evaluate the effects of two marine dietary supplements with a high calcium content: a fishbone powder (Phoscalim) and a ray cartilage hydrolysate (Glycollagene), in comparison with milk, and a placebo (maltodextrin), on calcium metabolism and a biochemical marker of bone resorption, using the oral calcium tolerance test. Subjects: Twenty male volunteers were randomized to eat 836 mg of calcium from different sources compared to maltodextrin during a Latin square study. Serum calcium concentrations and other parameters of the calcium metabolism, such as serum intact parathyroid hormone (iPTH) and serum C telopeptides (s-CTX), were measured after an acute oral calcium load based on the Pak protocol. Results: An increase in serum-corrected calcium areas under the curve (AUC) occurred with Phoscalim and Glycollagene when compared to milk. Significantly lower iPTH concentrations were observed with Glycollagene than with milk at T0+1 h, T0+3 h, T0+6 h and with Phoscalim than with milk at T0+6 h. A significantly lower s-CTX concentration was observed with Glycollagene than with milk and Phoscalim at T0+6 h. Furthermore, the urinary calcium/creatinine ratio increased significantly more with Glycollagen than with milk in T0 h+3 h and T3 h+6 h. Conclusion: These two dietary supplements from marine sources constitute oral calcium sources when compared to milk on calcium absorption and bone resorption markers on short time.